Modelling and Simulation of Chromatographic Processes for Whey Proteins - Jadhav, Sanket H. (Curtin University, 2019)
The research focuses on understanding implementation of modelling and simulation for ion exchange chromatography. A computational tool ExProSim:IC was developed in MATLAB2014b and literature based validation was performed for three thermodynamic models along with a mass transfer model. Furthermore, detailed analysis of separation characteristics for major and minor whey protein standards, and crude whey protein concentrate was performed for experimental validation of the tool giving a better understanding of model parameters for simulation of chromatographic operations.